Furofuran lignans and alkaloids from Clinacanthus nutans. Issue 9 (3rd May 2019) - Diao, Hong-Zhang; Chen, Wen-Hao; Cao, Jian; Shao, Tai-Ming; Song, Xiao-Ping; Han, Chang-Ri
Abstract: One new furofuran lignan 2-methoxy-9 β -hydroxydiasesamin (1 ), and four analogues (2 –5 ), together with eight alkaloids (6 –13 ), were isolated from the ethanol extract of the aerial part of Clinacanthus nutans . Their structures were elucidated by the detailed analysis of comprehensive spectroscopic data. All the compounds were isolated from the genus of Clinacanthus for the first time. In addition, lignans isolated from C. nutans was reported for the first time. Compound1 exhibited modest activity against three human tumor cell lines Hela, MCF-7, and A549, with IC50 values of 68.55, 60.00, and 59.17 μM, respectively. Abstract :